Moreno - Pablo, Crisaldo (Videoflick Productions, 2007)
When Cris arrives at the village of the T'boli in lake Sebu, South Cotabato, he thought he has left his dark recent behind. He is working on commission as a video documentarist to make a profile on the women T'boli and their changing views on multiple marriages. The most affluent men, called Datu, marry more than once and each time pays dowry to the family of the women they marry. When a young T'boli woman, Ngapon, tells Cris that she wants to free from a marriage that was set by her parents and to go to Manila, Cris begins to confront what he left in the city. Like the proud Datu with many wives, Cris has Denver, a bronze skinned lover in Manila, who is proud of his relationships. Denver lives with Cris in an apartment as partners yet he still goes into sexual and emotional relationships with other men. Ngapon's quest for freedom becomes Cris' journey to a very sad dark past.